TRANSLATION PROCEDURES OF MEDICAL TERMS IN THE BOOK ENTITLED STRESS LESS - Desak Nyoman Astri Pradnyani Putri (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2014)
This article aims at investigating the translation procedures of medical terms from English into Indonesian. The data of medical terms was taken from the book entitled Stress Less written by Colbert (2005) and the Indonesian version with the same title, translated by Wandaningsih (2006). This article applied qualitative research method. Observation method was applied at once with the implementation of note-taking technique. Informal and formal methods were applied to present the analyzed data in this article. The theory proposed by Newmark (1988) was applied to analyze the problem of procedures of translation. Newmark (1988) introduced eighteen translation procedures. The findings show that there were eleven translation procedures applied in translating the medical terms in the book Stress Less. The translation procedures were literal translation, transference, naturalization, descriptive equivalent, through-translation, shift, modulation, recognized translation, reduction and expansion, note and triplets. The application of those procedures was significantly influenced by readership aspect, where the target readers of the book are common people with many kinds of background.